Sports Pharmacy as an emerging health science field; A perspective on the global and national scope - Khan, Nida; Noushad , Shamoon; Ahmed , Sadaf (International Journal of Endorsing Health Science Research, 2018)
Background: Sports Pharmacy is an emerging field globally that has developed from in connection with health, economic and social sectors. The main reason of its importance has been taken into account for research and implementation in the prevention of doping, delivery systems, compounding medications and dietary supplements. Though there is a dire need of developing f sports Pharmacy as a separate field in Pakistan and to address hindrances in its progress. Methodology: A short communication of 20 years i.e. 1998-2018. Databases used are Google Scholar, PubMed, Research gate, Scopus, The Nation news, BBC news. Results: The significant highlights include that there is a usual partaking of the populace in sport and exercise at personal and professional levels and at every level, there is a need for advice about general healthcare and associated therapies for better performance and wellbeing. It is also identified that there is a growing need for specialist pharmacists in the area of sport and exercise in order to fulfill this valuable healthcare role. These specialists may be described as sports pharmacist’s development of Sports pharmacy in Pakistan. Prevention of doping worldwide reduced significantly with the help of pharmacist expertise. Conclusion: Sports pharmacy can be helpful in changing some healthcare aspects regarding sports worldwide. For the development of sports pharmacy in Pakistan, serious arrangements need to be taken.